The intellect: an equivocal concept - Ssuna, Salim (2020)
The centrality of the intellect is recognized by all cultures and civilizations. This appeals to scholars of various inclinations to delve into its study in terms of its entity, nature, function, location in the human body, and how it relates and influences the functioning of other organs of the body and above all the forces behind it. Given this uniqueness of the intellect, one would expect during advanced scientific age characterized by scientific studies to have this significant concept well defined. The opposite is true as this concept up to date is among the most misconstrued concepts even with a multiplicity of researched conducted over a century. The current study aims at analysing how this concept is defined by Classical Muslim Philosophers, Modern Cognitive Psychologists and finally the Quranic view. The study will focus on the critical analysis of the opinions of these groups on how they define and understanding the intellect. This is a qualitative study and it will use textual analysis methodology. The study notes varying disparities in defining and understanding of the intellect as it is based on a multiplicity of sources and philosophies. A Quranic outlook plays a significant role in clarifying the connotation of this concept as it is based on a Revelation and Sunnah of the Prophet, (pbuh), a source that can provide a solution to this paradox.